The Realization of Interpersonal Meaning in Arabic–Indonesian Command Speech Acts of Farha Movie: A Systemic Functional Linguistics Study - Zahra Aulia Hanifa; Mohamad Zaka Al Farisi; Rinaldi Supriadi (The Doctoral Studies Program of Linguistics of Udayana University, 2026)
This study aims to examine how interpersonal meaning in Arabic command speech is realized in the film Farha (2021) and how it is transferred into Indonesian subtitles. Employing a descriptive qualitative method, the research draws on Systemic Functional Linguistics (SFL) and directive speech act theory to analyze 117 command clauses taken from the film and its official subtitles. Each clause was examined through the interpersonal categories of mood, obligation, polarity, person, and tenor to assess the strength and equivalence of illocutionary force across languages. The findings indicate a predominant use of imperative mood, high obligation, positive polarity, and second-person forms, reflecting direct and hierarchical communication typical of conflict settings. Overall, the Indonesian subtitles maintain the core interpersonal force of the Arabic source text, though some shifts occur in obligation intensity, command merging, and lexical choices. This study contributes a systematic model for evaluating interpersonal equivalence in Arabic–Indonesian audiovisual translation.